Exploring the human digestive system through ARSIPERSIA augmented reality insights - Timothy John Pattiasina; Edwin Meinardi Trianto; Raymond Sutjiadi; Jacinda Ariella (Universitas Muhammadiyah Malang, 2024)
As times evolve, numerous advanced technologies emerge to support human activities. Augmented reality, a technology that integrates virtual objects with real-world elements in the physical environment, is particularly noteworthy. In the field of education, augmented reality is widely applied to enhance the interactivity of the teaching and learning process. This study endeavours to create an application focused on the human digestive system, with the aim of presenting digestive organs in three dimensions. Unlike traditional learning media, which typically feature two-dimensional images or videos of digestive organs, the Augmented Reality Human Digestive System (ARSIPERSIA) application addresses the challenge of visualizing authentic human digestive organs. Unity 3D and Vuforia were employed in the development of this application. The application underwent comprehensive testing through two methodologies: black box testing and usability testing. The results of the black box testing affirm the effective functionality of the application, covering tasks such as image target scanning, information display, and interactive quizzes. Usability testing findings indicate that ARSIPERSIA facilitates students in visualizing human digestive organs, provides relevant information, enhances comprehension of the digestive system, and sparks students' interest and motivation through captivating learning media.